Sexual Conversation Networks and Young Adults’ Sexual Health in a Southeast-European Context - Božić, Jasmina (Array, 2011)
Social network approach has conceptually and empirically improved research on HIV/AIDS by counterbalancing the individualized concepts of sexual decision-making. In the current study, associations between the structural characteristics of ego-centered networks and HIV-related knowledge, attitudes, and behaviours were examined in a population-based sample (n = 1005) of young Croatian adults aged 18 - 25 years. The findings suggested that the associations between the selected HIV-relevant outcomes and the structural properties of social networks were weak and markedly gender-specific. Among women, network-based religiosity predicted HIV-related knowledge, while network density was related to attitudes toward condoms. Age homophily and network history were correlated with condom use at last intercourse among men. Future studies may improve the understanding of the associations between social networks and HIV-relevant beliefs and behaviours by exploring the possibility that network effects are not invariant over time.